2021
DOI: 10.1186/s12885-021-08276-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression identifies a transcriptional regulatory network involving ER-alpha and PITX1 in invasive epithelial ovarian cancer

Abstract: Background The heterogeneous subtypes and stages of epithelial ovarian cancer (EOC) differ in their biological features, invasiveness, and response to chemotherapy, but the transcriptional regulators causing their differences remain nebulous. Methods In this study, we compared high-grade serous ovarian cancers (HGSOCs) to low malignant potential or serous borderline tumors (SBTs). Our aim was to discover new regulatory factors causing distinct biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 88 publications
1
3
0
Order By: Relevance
“…Analogous to the observations in breast cancer, the interaction between PITX1 and ERa has been substantiated in ovarian cancer cell lines (72). While ERa's pivotal engagement in the PI3K/AKT and RAS/ERK signaling pathways within the context of ovarian cancer has undergone extensive elucidation, the present study refrained from delving into the specific functions of PITX1 and ERa in this ovarian cancer context (73).…”
Section: Ovarian Cancersupporting
confidence: 51%
“…Analogous to the observations in breast cancer, the interaction between PITX1 and ERa has been substantiated in ovarian cancer cell lines (72). While ERa's pivotal engagement in the PI3K/AKT and RAS/ERK signaling pathways within the context of ovarian cancer has undergone extensive elucidation, the present study refrained from delving into the specific functions of PITX1 and ERa in this ovarian cancer context (73).…”
Section: Ovarian Cancersupporting
confidence: 51%
“…Previous research on PITX1 in cancer has revealed cancer-type-specific effects. While upregulation of PITX1 has been shown to be associated with tumor progression in lung adenocarcinoma 31 , kidney renal clear cell carcinoma 32 , breast 33 , epithelial ovarian 34 , and prostate 35 cancer, interestingly, in other cancer types, such as melanoma 36 , ESCC 37 , osteosarcoma 38 and head and neck squamous cell carcinoma 39 , down-regulation of PITX1 has been found to enhance tumor progression. Other EMT-related genes exclusively present in our signature included two long-non-coding RNA genes: ABHD11-AS1 and BCYRN1 .…”
Section: Discussionmentioning
confidence: 99%
“…The PDGFC, SERPINE2, TSPAN1, ANK1, and SYNPO are involved in cell migration and cytoskeleton organization. 40…”
Section: Gene Expressionmentioning
confidence: 99%